Persepsi Guru Terhadap Implementasi Teknik Penilaian Non-Tes Dalam Pembelajaran Kelas X Di MA Al Mansur Popongan - Annisa Arianti; Aji Joko Budi Pramono (Alpatih Harapan Semesta, 2026)
This study aims to analyze teachers' perceptions of the implementation of non-test assessment techniques in Islamic Religious Education (PAI) learning for grade X at MA Al Manshur Popongan. The study used a descriptive qualitative approach with a field research type. The research subjects consisted of five grade X PAI teachers who were selected purposively. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The data analysis process was supported by the R Program through the stages of open coding, axial coding, and selective coding. The results showed that teachers had a positive perception of the implementation of non-test assessment because it was able to assess students' affective and psychomotor aspects more comprehensively. The dominant assessment techniques used included observation, worship practices, presentations, attitude journals, group projects, and portfolios. The implementation of non-test assessment had a positive impact on increasing student activity, discipline, and self-confidence in learning. However, its implementation still faces various obstacles, such as time constraints, administrative burdens, large student numbers, and difficulties in preparing assessment rubrics. This study confirms that strengthening teacher competencies and digitalizing the assessment system are important factors in optimizing the implementation of non-test assessments in madrasas.